OG‘ZAKI VA YOZMA NUTQNI O‘STIRISHDA KO‘CHMA MA’NOLI SO‘ZLAR VA TASVIRIY IFODALARDAN FOYDALANISH - Eshimbetov, O. (SCIENCE and SOCIETY, 2025)
The article offers recommendations for increasing the vocabulary by purposefully teaching younger schoolchildren phrases, visual expressions and other lexical means, the main thing is to make exercises and tasks for the formation of coherent speech, as well as ways to select text.
Keywords: connective speech; figurative meanings of words; descriptive expression; phrase; exercise; task; lesson; vocabulary